Culture, Education and Truth. The Perspectives on Help Offered to Contemporary Youth - Królikowski, Janusz (Teologia w Polsce, 2020)
This paper focuses on three fundamental notions-realities which describe human life and constitute at the same time its foundation and the space of participation in it. The triad culture – education – truth describes the most essential human experiences, simultaneously, defining the direction of their deepening and creative developing. Certainly, in the times like these when everything is questioned notions-experiences that belong to this triad are not problem-free. What is more, they are deemed to be superfluous, especially in ultra-left-wing ideologies in which suicidal tendencies are easily discernible. Taking this into consideration, it is hardly possible to avoid polemic attitude towards numerous questions even those most essential since in their semantic field the greatest confusion may be detected. That is why there are numerous attempts to answer the question how, in the face of such a dynamic spiritual condition of the world, those fundamental issues can be dealt with within the frames of anthropology, and how they can be justified from the anthropological point of view. This reflection is rather philosophical in character, however, it is also inspired by the fundamental Christian truth which says about the incarnation of the Son of God and about the salvation of man made by Him.